Examination of Ergonomics Appropriateness of Primary Schools in Rivers State (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The study used the descriptive survey design to examine the ergonomic appropriateness primary schools Rivers State. Simple random and stratified sampling techniques were used to choose 498 Basic 4 pupils from 29 classes of 20 schools in 5 local government areas of Rivers state and their teachers. The instrument used for the study examination of available school documents and interview of teachers. The study had 4 research questions. The research questions were answered with tables and charts. The result showed that there was ergonomic appropriateness in Class size of Basic 4 pupils as the class size was well within the recommended 35. The result, however, showed that age of pupils, teacher qualification and curriculum usage were not ergonomically appropriate. Recommendations were made for the study to maintain the small class size observed in schools; provide constant training for teachers without the necessary qualifications and encourage them to upgrade their qualifications, while emphasising the employment of professionally qualified teachers; enrol students who are age appropriate and academically capable in primary education programmes, and ensure curriculum appropriateness.